(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
The tourism industry worldwide is growing rapidly to meet the demands of global tourists, but its facilities remain limited and urgently need improvement. The main focus of this study was to examine twenty-four (N = 24) empirical, open-access articles that primarily discuss the role of AI in facilitating customer service in the tourism industry. This study is significant for the Nepalese academic community because there is no reliable research in this domain demonstrating that AI helps the tourism industry flourish and meet customers’ needs for experiences and services. The data from the selected articles were downloaded after obtaining consent from the authors and publishers. The results show that empirical research did not address the moral problems associated with the use of AI in the tourism industry. The findings highlight research gaps in AI for hospitality and tourism, notably an overreliance on secondary data lacking empirical validation, leading to unreliable results. This study could struggle to forecast without empirical support. Empirical evidence indicates a significant knowledge gap stemming from the limited scope of ethical analysis, underdeveloped theoretical linkages between artificial intelligence and tourism development, and inadequate exploration of AI-tourism interactions beyond purely technological dimensions. The results are useful for people working in the tourism industry, as they recognise the necessity of AI’s positive role in supporting mental health. The analysis is based on a limited selection of papers, leading to a lack of critical examination.